2003
DOI: 10.1128/jvi.77.6.3557-3568.2003
|View full text |Cite
|
Sign up to set email alerts
|

3′ Nontranslated RNA Signals Required for Replication of Hepatitis C Virus RNA

Abstract: We describe a mutational analysis of the 3 nontranslated RNA (3NTR) signals required for replication of subgenomic hepatitis C virus (HCV) RNAs. A series of deletion mutants was constructed within the background of an HCV-N replicon that induces the expression of secreted alkaline phosphatase in order to examine the requirements for each of the three domains comprising the 3NTR, namely, the highly conserved 3 terminal 98-nucleotide (nt) segment (3X), an upstream poly(U)-poly(UC) [poly(U/UC)] tract, and the var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
182
1
3

Year Published

2005
2005
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(193 citation statements)
references
References 52 publications
(84 reference statements)
7
182
1
3
Order By: Relevance
“…3). It has been reported that the length and composition of the poly(U/UC) tract is important for the replication of HCV replicons (Friebe & Bartenschlager, 2002;Yi & Lemon, 2003;You & Rice, 2008). However, no replication advantage of a poly(U/UC) tract longer than 86 bp was revealed in this study.…”
Section: Discussioncontrasting
confidence: 41%
See 2 more Smart Citations
“…3). It has been reported that the length and composition of the poly(U/UC) tract is important for the replication of HCV replicons (Friebe & Bartenschlager, 2002;Yi & Lemon, 2003;You & Rice, 2008). However, no replication advantage of a poly(U/UC) tract longer than 86 bp was revealed in this study.…”
Section: Discussioncontrasting
confidence: 41%
“…Each segment of HCV was cloned into this vector to generate the full-length clones. The HCV-KT9 clone was established using the 39-terminal fragment with the longest poly(U/UC) tract length (115 nt), which should have a high replication ability (Friebe & Bartenschlager, 2002;Yi & Lemon, 2003;You & Rice, 2008). A clone with a shorter poly(U/UC) tract length (86 nt), HCV-KT1, was also generated.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The HCV polyU/UC region is a flexible motif among HCV strains and is essential for viral replication 13 . In the HCV genotype 1b strain used in these experiments, the poly-U/UC region is comprised of 100 nt containing 78% uridine and 22% ribocytosine (Fig.…”
mentioning
confidence: 99%
“…The HCV genome is a positivestranded Ϸ9.6-kb RNA molecule consisting of a single ORF, which is flanked by 5Ј and 3Ј untranslated regions (UTR). The HCV 5Ј UTR contains a highly structured internal ribosome entry site (3)(4)(5)(6)(7)(8), and the 3Ј UTR is essential for replication (9,10). The HCV ORF encodes a single 3,008-to 3,037-aa polyprotein that is posttranslationally processed to produce Ն10 different proteins: core protein, envelope proteins E1 and E2, p7, and nonstructural proteins NS2, NS3, NS4A, NS4B, NS5A, and NS5B (1,8,11).…”
mentioning
confidence: 99%